DINAMIKA TANTANGAN POLITIK DALAM ERA DEMOKRASI INDONESIA - Fauzan Hamidi; Vina Karina Putri; Ahmad Burhanuddin; Aida Fitriani (Yayasan Baitul Hikmah al-Zain, 2024)
This article discusses the political challenges facing Indonesia in the post-reform democratic era. The main focus is on issues such as corruption, political polarization, the role of social media in shaping public opinion, and social movements. This research uses a qualitative method with a descriptive-analytical approach, where data is obtained from various literature sources and case studies. The results show that corruption remains a systemic problem that hinders the development of democracy, while political polarization exacerbated by social media creates social tensions. Social media plays a dual role as a platform for political participation as well as the spread of disinformation. In addition, social movements show that civil society has significant power in influencing government policy. This article seeks to provide a comprehensive picture of Indonesia's current political dynamics and emphasizes the importance of collaborative efforts to overcome these challenges in order to strengthen democracy in Indonesia.